Paleoproterozoic UHT metamorphism with isobaric cooling (IBC) followed by decompression–heating in the Khondalite Belt (North China Craton): New evidence from two sapphirine formation processes. (19th February 2020) - Jiao, Shujuan; Guo, Jinghui
Abstract: Interpretation of reaction microstructures may provide constraints on the P – T path followed by rocks, with implications for the geodynamic evolution. Sapphirine generally occurs in diverse microstructures in ultrahigh‐temperature (UHT) Mg–Al‐rich granulites. Understanding multi‐stage sapphirine formation processes and the resultant P – T path may provide insights into the cause of UHT metamorphism, which is otherwise under broad debate. Here, we investigate samples of UHT granulite containing two distinct types of sapphirine from the Dongpo locality in the Khondalite Belt, North China Craton, with the aim of understanding the processes of sapphirine formation and the metamorphic evolution of the host rocks. Petrographic observations show that early sapphirine, which occurs as coronas on spinel and as single porphyroblasts, formed together with biotite, sillimanite, and inclusion‐rich garnet. Late symplectitic sapphirine along with fine‐grained plagioclase and spinel plus plagioclase symplectites, formed by consumption of sillimanite, biotite, and garnet. Three pseudosections based on the bulk compositions of microdomains inferred to reflect spatially restricted equilibrium suggest that the rocks record near isobaric cooling (IBC) from ~980 to 830ºC at ~0.9 GPa for early sapphirine formation, and decompression and heating to ≤0.7 GPa and ~900ºC for late sapphirine formation. Our study in combination with other metamorphic P–T and age information reveals the common occurrence of IBC paths and long duration ( c . 1.93 to 1.86 Ga) regional UHT metamorphism in the Khondalite Belt, North China Craton. Locally, this is followed by decompression – heating paths at c . 1.86 Ga. The Palaeoproterozoic UHT metamorphism with long‐lived IBC path in the Khondalite Belt, North China Craton supports large hot orogen model in the amalgamation of this part in the supercontinent Nuna.